MENINGKATKAN MINAT BELAJAR SISWA DALAM PELAJARAN IPA MATERI GERAK BENDA DENGAN METODE EKSPERIMEN DIKELAS III A SD NEGERI 066652 BAKTI LUHUR MEDAN HELVETIA - Rezki, Fitri; Sitorus, Nensi (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2018)
This study aims to increase student interest in learning science subjects by using experimental learning methods. This research includes classroom action research (CAR), which is a type of research conducted by teachers to solve classroom learning problems. The subjects of the study were students of class IIIA at SD Negeri 066652 devoted to noble with 20 students. Data collection techniques conducted in this study through observation, documentation and questionnaires. This activity begins with planning, implementing actions, observing and reflecting.The results showed an increase in student interest in learning that has an impact on student learning outcomes so that there is an increase in science subject matter of motion objects. This can be seen from the results. Pre-cycle questionnaire 29.25%, 64.5% in the first cycle and 89.5% for the second cycle. The percentage of teacher activity in the first cycle was 67.5%, the second cycle was 87.5%, then the percentage of the results of the students' activities in the first cycle was 76.3% and the second cycle was 81.5%. The conclusion of this study is that the experimental method can increase student interest in class IIIA Public Elementary School 066652 devoted to noble T.A 2018/2019.